Analisis Risiko Paparan Kadmium dan Kromium Melalui Konsumsi Kerang Bakalang pada Kelompok Lanjut Usia di Lantebung, Makassar - Zikrina, Nadya Nur; Gafur, Abd.; Syam, Nasruddin (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Bakalang clam is an important protein source for coastal communities; however, heavy metal contamination may pose health risks, especially to vulnerable elderly populations. This study aims to analyze the non-carcinogenic health risk resulting from cadmium (Cd) and chromium (Cr) exposure through the consumption of bakalang clams by the elderly in the Lantebung coastal area, Kelurahan Bira. Heavy metal concentration data were obtained through laboratory analysis, while consumption data and respondent characteristics were collected through direct surveys. Daily intake was calculated based on consumption frequency and duration, body weight, and averaging time. The Risk Quotient (RQ) was calculated by comparing daily intake with the reference dose (RfD). The results showed that the average concentrations of Cd and Cr in bakalang clams were 0.08 mg/kg and 1.04 mg/kg, respectively. The daily intake values for Cd and Cr were 0.00392 mg/kg/day and 0.051 mg/kg/day, respectively. The RQ values for Cd and Cr were 3.92 and 17.0, indicating a significant potential health risk. This study concludes that the consumption of bakalang clams contaminated with Cd and Cr poses a potential non-carcinogenic health risk to the elderly population in the study area.